Sumatran tiger density estimates in the Leuser Ecosystem, Sumatra, Indonesia - Figel, Joe J.; Akbar, M. Ibnu; Khairi, Kamal; Darmansyah,; Pian, Muhammad; Supiyandi,; Suhaili,; Abidin, Zainal; Aritanoga, M. Randa; Ali, Karim; Reduan,; Rhomadani,; et al. (Frontiers in Conservation Science, 2025)
Density is a fundamental parameter for monitoring animal populations and determining actions for habitat management. We investigated sex-specific densities of critically endangered Sumatran tigers (Panthera tigris sumatrae) in provincially protected forests outside the National Park system in the Leuser Ecosystem of Indonesia. Sumatran tiger camera trap studies are characterized by imprecise density estimates derived from excessively sparse 90-day datasets, reflecting the challenges of obtaining adequate sample sizes on this rainforest carnivore. We overcame this obstacle with strategic reconnaissance, recruitment of highly skilled forest rangers, and deployment of infrequently used professional-grade camera traps. We used closed population spatial capture-recapture (SCR) models based on data from 52–64 paired camera stations to estimate densities of male and female Sumatran tigers, comparing results between 90-day and 180-day sessions. Camera trapping for 12-months (June–December 2023 and May–November 2024) accumulated 282 identifiable photographs, including 245 recaptures, of 27 adult tigers (14 females, 12 males, and 1 individual of unknown sex); average captures (recaptures) were 85 (67) and 141 (123) for the 90 and 180-day periods, respectively. Cumulatively, these results represent the most robust single-study Sumatran tiger camera trap dataset. During the 90-day sessions, sex-specific tiger densities ranged from 0.97 (± 0.37)–1.83 (± 0.59) female and 0.56 (± 0.22)–0.61 (± 0.29) male tigers. During the 180-day sessions, estimates were only negligibly more precise, ranging from 0.94 (± 0.33)–1.76 (± 0.54) female and 0.41 (± 0.15)–0.50 (± 0.22) male tigers. Across both years, densities were 1.42–2.35 tigers/100 km², about 2.5–4.1 times greater than the most recent estimates in the mountains of Gunung Leuser National Park. Our results support prioritization of spatial over temporal sampling for population monitoring of rare and elusive species as expanding the trap array resulted in greater precision of density estimates than extending the sampling period.